2022
DOI: 10.1097/wnn.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis Mimicking Behavioral Variant of Frontotemporal Dementia in a 59-Year-Old Man

Abstract: We present the case of a man exhibiting a clinical phenotype of behavioral variant of frontotemporal dementia (bvFTD). The man had developed psychiatric disturbances with verbal aggressiveness over a few months, followed by cognitive and frontal behavioral disorders, fulfilling the clinical criteria for bvFTD. Atrophy and hypometabolism in frontotemporal regions were consistent with the diagnosis. However, serum-screening exams for syphilis infection were positive, and CSF analysis, despite a negative Venereal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In another case, Caroppo et al described the findings of a 59-year-old man who presented with clinical symptoms of a behavioral variant of frontotemporal dementia [ 16 ]. The patient developed psychiatric disturbances with verbal aggressiveness over the course of a few months, which was followed by cognitive and behavioral disorders.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case, Caroppo et al described the findings of a 59-year-old man who presented with clinical symptoms of a behavioral variant of frontotemporal dementia [ 16 ]. The patient developed psychiatric disturbances with verbal aggressiveness over the course of a few months, which was followed by cognitive and behavioral disorders.…”
Section: Reviewmentioning
confidence: 99%
“…Screening exams for syphilis turned out to be positive in subsequent testing, and there were abnormal CSF findings which pointed to neurosyphilis as the diagnosis. With antibiotic treatment, the patient's behavioral symptoms along with cognitive impairments showed marked improvement, confirming neurosyphilis as the cause of the psychiatric disturbance [ 16 ]. This case illustrates that neurosyphilis can mimic frontotemporal dementia and should, therefore, be kept high on the differential diagnosis as treatment can halt disease progression and lead to remarkable improvement in the disease course.…”
Section: Reviewmentioning
confidence: 99%
“…Although these cases provide valuable information, there are certain aspects to consider. In their cerebrospinal fluid (CSF) analysis during treatment, Prynn et al [ 10 ] and Caroppo et al [ 11 ] found negative results for syphilis infection, while serum screening exams for syphilis infection returned positive. Additionally, while both cases showed significant cognitive improvement shortly after treatment, Prynn et al [ 10 ] did not conduct follow-up neuropsychological testing or provide a detailed behavioral description.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while both cases showed significant cognitive improvement shortly after treatment, Prynn et al [ 10 ] did not conduct follow-up neuropsychological testing or provide a detailed behavioral description. In the case of Caroppo et al [ 11 ], the man’s behavioral disorders resurfaced 2½ years aftertreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation